Marketing Strategy Analysis Of Arco Azka Manna Kitchen Msmes, Bengkulu Selatan - Devi Arsianti; Siti Hanila; Eska Prima Monique Damarsiwi (Penerbit Jurnal Indonesia, 2021)
Pursuant to result of calculation of internal factor and strategy ekternal marketing of UMKM Snack Kitchen of Arco Azka got by co-ordinate value for kuadran analyse internal SWOT score wight ( 5,62) and score wight of eksternal ( 5,77). Pursuant to each calculation of kuadran above indicating that biggest value reside in at SO kuadran that is 6,72. The value obtained from calculation of strength score and opportunity score, where company maximize internal strength which owned by an company by exploiting existing opportunity. Kuadran analyse SWOT applying of strategy marketing of UMKM Snack Kitchen of Arco Azka show its position reside in at I kuadran, that strategy the yielded is strategy of SO, that is organization have the power of and opportunity where organization in a state of settled and prima. Conducive organization to continue to ekspansi, enlarging growth and reach for progress maximally. compatible strategy is (penetration of market and development of market) and product development in this time, is so that diversified by konsentrik can lessen risk related to narrow;tight product lini.